Prediction of plant diversity under different stocking rates based on functional traits of constructive species in a desert steppe, northern China - Li, Jiangwen; He, Bangyin; Zhou, Shuangxi; Zhang, Xiaoxi; Li, Cai; Han, Guodong (Frontiers in Ecology and Evolution, 2022)
Excessive grazing causes a decrease in plant diversity of grassland and also leads to changes in the functional traits of grassland plants. Based on the relationship between plant diversity and the functional traits of constructive species, the patterns of change in plant diversity can be predicted based on change in plant functional traits under different stocking rates. For the present study, Stipa breviflora desert steppe in Inner Mongolia was studied to characterize the plant community and population characteristics and plant functional traits of S. breviflora in grazing areas with different stocking rates [without grazing, light grazing (LG, 0.93 sheep unit hm-2half∙yr-1), moderate grazing (MG, 1.82 sheep unit hm-2half∙yr-1), heavy grazing (HG, 2.71 sheep unit hm-2half∙yr-1)]. The results showed that: (1) LG significantly weakened the competitive advantage of the constructive species (S. breviflora) (P<0.05),while HG significantly strengthened its competitive advantage in the community (P<0.05); (2) Changes in plant diversity were generally significantly related to changes in S. breviflora root traits. The competitive advantage of S. breviflora in the community and the change in root traits could be used to predict the change in plant diversity in the desert steppe under different stocking rates. This research can provide a theoretical basis for maintaining plant diversity and sustainability in the desert steppe.